Rural institutions dealing with the conservation of water resources in the microwatershed of the Caquijá River, Sierra Santa Cruz, Izabal, Guatemala - Arrecis López, Eugenia M. (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006